Music Education and the Art of Performance in the German Baroque - Butt, John 1960- (Cambridge Cambridge University Press, 1994)
In considering the role of practical music in education this book explores the art of performance in Germany during the Baroque period. The author examines the large number of surviving treatises and instruction manuals used in the Lutheran schools during the period 1530-1800 and builds up a picture of the function and status of music in both school and church. This understanding of music as a functional art--musica practica--in turn gives us insight into contemporary performance of the sacred work of Praetorius, Schütz, Buxtehude or Bach.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Historically informed performance; Music performance technique; Music history; Music education; Lutheranism; Germany